The Hermeneutics of the Scriptural Citations in Hebrews 2:12-13 - De Sousa, Rodrigo Franklin; Collins, Adela Yarbro 1945- (2019)
The purpose of this contribution is to discuss the biblicalcitations in Heb 2:12–13 to better understand the hermeneuticsof the author of Hebrews. The passage contains threecombined citations taken from two different passages, Ps 21:23LXX (22:23 MT) and Isa 8:17–18 LXX. The discussion centerson how these citations fit in the flow of the epistle’s argumentand how the author saw the connection between them. Thestudy suggests that we need to develop approaches that sharpenour understanding of what “context” means in the author’s ownhermeneutical horizon. I argue that the context in the light ofwhich the author interpreted these verses is primarily a theologicalone, and while it incorporates elements of the historicaland literary contexts of the verses, it must be treated accordingto its own specificities.
Keywords: Bibel; Bible. Hebrews; Criticism, Textual; Bible. Isaiah; Criticism, Literary; Bible. New Testament; Relation to Old Testament; Bible. Psalms; Criticism, Literary; Hermeneutics; Resurrection; Biblical teaching